2018
DOI: 10.1371/journal.pone.0196541
|View full text |Cite
|
Sign up to set email alerts
|

Potential involvement of the 18 kDa translocator protein and reactive oxygen species in apoptosis of THP-1 macrophages induced by sonodynamic therapy

Abstract: Sonodynamic therapy (SDT) with exogenous protoporphyrin IX (PpIX) or endogenous PpIX derived from 5-aminolevulinic acid (ALA) has been carried out to produce apoptotic effects on macrophages, indicating a potential treatment methodology for atherosclerosis. Our previous studies have found that mitochondria damage by reactive oxygen species (ROS) plays a major role in the SDT-induced apoptosis. This study aimed at investigating the potential involvement of the mitochondrial 18 kDa translocator protein (TSPO) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Taking into account that TSPO is also involved in alterations of cytosolic cholesterol levels, there is also a possibility for its involvement in modulation of α-Syn aggregation rates. Connection has also been established between TSPO binding capacity and ROS levels, which are as mentioned earlier one of the reasons for PD development [89,90]. In accordance with these findings, Gatliff et al reported that SH-SY5H cells exhibited enhanced ROS production after TSPO overexpression establishing connection between TSPO, VDAC, and Ca 2+ homeostasis [91].…”
Section: α-Synuclein Lipid Homeostasis and Tsposupporting
confidence: 64%
“…Taking into account that TSPO is also involved in alterations of cytosolic cholesterol levels, there is also a possibility for its involvement in modulation of α-Syn aggregation rates. Connection has also been established between TSPO binding capacity and ROS levels, which are as mentioned earlier one of the reasons for PD development [89,90]. In accordance with these findings, Gatliff et al reported that SH-SY5H cells exhibited enhanced ROS production after TSPO overexpression establishing connection between TSPO, VDAC, and Ca 2+ homeostasis [91].…”
Section: α-Synuclein Lipid Homeostasis and Tsposupporting
confidence: 64%
“…Other cell types should be chosen for the study but we elected to use it since THP-1 macrophages were used by some researchers. 34,35 We also need further studies in human blood-derived macrophages and mouse models to confirm our conclusion.…”
Section: F I G U R Ementioning
confidence: 78%
“…Herein, another pro-inflammatory signaling parameter explored was the level of the reactive oxygen species. The treatment with PK-11195 has been reported to decrease ROS production in human macrophages [73] and in murine microglia [48]; herein, TSPO ligands were able to modulate the production of ROS in human microglia too. Although the mechanism of TSPO regulation of ROS production is still under debate, the obtained results supports that this ability is not related to steroidogenesis stimulation.…”
Section: Discussionmentioning
confidence: 93%